2004
DOI: 10.1124/mol.65.2.426
|View full text |Cite|
|
Sign up to set email alerts
|

Agonist Binding and Gq-Stimulating Activities of the Purified Human P2Y1 Receptor

Abstract: The human P2Y 1 receptor (P2Y 1 -R) was purified after high-level expression from a recombinant baculovirus in Sf9 insect cells. Quantification by protein staining and with a radioligand binding assay using the high-affinity P2Y 1 -R antagonist [ binding assays for antagonists with the purified P2Y 1 -R were in good agreement with the K i and K B values determined for these molecules in membrane binding and activity assays, respectively. Availability of P2Y 1 -R in purified form allowed direct determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 41 publications
6
82
0
Order By: Relevance
“…We have focused on the subset of reactions that govern ADP-mediated phosphoinositide signaling and mobilization of intracellular Ca 2ϩ ( Table 1). The P2Y 1 receptor is coupled primarily to the G q family of G proteins, 20,21 which activate the beta-isoform of phospholipase C. 1,20 Previous work has shown that this pathway accounts for more than 90% of the ADP-mediated Ca 2ϩ signaling in platelets. 22 To eliminate Ca 2ϩ influx and the need to model store-operated Ca 2ϩ entry, we used experimental data from studies in which extracellular Ca 2ϩ was removed by ethylenediaminetetraacetic acid (EDTA) or another chelating agent.…”
Section: Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We have focused on the subset of reactions that govern ADP-mediated phosphoinositide signaling and mobilization of intracellular Ca 2ϩ ( Table 1). The P2Y 1 receptor is coupled primarily to the G q family of G proteins, 20,21 which activate the beta-isoform of phospholipase C. 1,20 Previous work has shown that this pathway accounts for more than 90% of the ADP-mediated Ca 2ϩ signaling in platelets. 22 To eliminate Ca 2ϩ influx and the need to model store-operated Ca 2ϩ entry, we used experimental data from studies in which extracellular Ca 2ϩ was removed by ethylenediaminetetraacetic acid (EDTA) or another chelating agent.…”
Section: Model Overviewmentioning
confidence: 99%
“…In that assay, Waldo and Harden combined purified human P2Y 1 , ADP, G ␣ and G ␤␥ subunits, PLC-␤ or RGS4, and radiolabeled GTP in large phospholipid vesicles and measured the agonist binding and G q -stimulating activities of the receptor. 21 GTPase activity was measured with and without agonist ( Figure 4B). ADP dose-response was measured with and without GAP protein ( Figure 4C).…”
Section: Signal Attenuationmentioning
confidence: 99%
“…Molecular cloning has identified seven mammalian P2X receptor subunits: P2X1, P2X2, P2X3, P2X4, P2X5, P2X6 and P2X7 [3], while eight mammalian P2Y receptors have been identified: P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , P2Y 12 , P2Y 13 and P2Y 14 [4]. P2X receptors are activated by adenosine-5′-triphosphate (ATP) and its stable, and consequently more potent, analogue αβ-methylene-ATP (αβ-meATP) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…P2X receptors are activated by adenosine-5′-triphosphate (ATP) and its stable, and consequently more potent, analogue αβ-methylene-ATP (αβ-meATP) [5,6]. P2Y receptors can be divided on the basis of their endogenous agonists into adenine nucleotide-preferring (P2Y 1 , P2Y 11 , P2Y 12 and P2Y 13 ) receptors and uracil nucleotide or UDP-sugar-preferring (P2Y 2 , P2Y 4 , P2Y 6 and P2Y 14 ) receptors [7]. Among the adenine nucleotide group, the human P2Y 11 receptor is selectively activated by ATP and fails to respond to adenosine-5′-diphosphate (ADP) [8], although the dog orthologue responds to both ADP and ATP [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation